The Star, 23 June 2008 - McIntyre, Ian (Star Publications (Malaysia) Berhad, 2008)
Politician should refrain from openly proposing the Islamic state concept because it can lead to confusion, Perlis Mufti Dr Mohd Asri Zainul Abidin said.